Applications of Indocyanine Green (ICG) fluorescence in pediatric colorectal conditions - Ismael Elhalaby; Elizaveta Bokova; Seth Saylors; Irene Isabel P. Lim; Rebecca M. Rentea (Elsevier, 2024)
Postoperative success in pediatric colorectal surgery hinges on achieving adequate perfusion during complex reconstructive procedures. This review synthesizes findings from recent publications regarding the application of Indocyanine Green (ICG) in various surgical interventions for conditions such as Hirschsprung disease, anorectal malformations, cloacal reconstructions, and others.Preliminary evidence suggests that ICG fluorescence enhances intraoperative decision-making by improving vascular visualization and assessing tissue perfusion. Compared to conventional methods, ICG may offer superior evaluation of intestinal perfusion.While initial reports indicate a favorable safety profile for ICG use in pediatric patients, further prospective studies are needed to confirm these observations, quantify benefits, and assess its impact on surgical outcomes. By providing real-time perfusion data, ICG holds promise for enhancing surgical precision and improving patient outcomes in pediatric colorectal surgery.